Pharmacodynamics and pharmacokinetics of ketoprofen enantiomers in sheep - Arifah, Abdul K.; Landoni, Maria F.; Frean, Stephen P.; Lees, Peter (American Veterinary Medical Association, 2001)
Objective - To establish pharmacokinetic and pharmacodynamic properties of a racemic mixture and individual R(-) and S(+) enantiomeric forms of ketoprofen (KTP) in sheep and determine pharmacodynamic variables of KTP by pharmacokinetic-pharmacodynamic modeling. Animals - 8 female Dorset crossbred sheep. Procedure - A tissue cage model of inflammation was used. Carrageenan was administered into tissue cages. Time course of cyclooxygenase (COX)-2 inhibition was determined in vivo by measurement of exudate prostaglandin E2 (PGE2) concentrations. Time course of COX-1 inhibition was determined ex vivo by measurement of serum thromboxane B2 (TXB2) concentrations. In addition, plasma concentration-time course and penetration of KTP enantiomers into inflammatory exudate and transudate (noninflamed tissue cage fluid) were investigated. Four treatments were compared: placebo, racemic mixture (rac-KTP [3 mg/kg of body weight, IV]), S(+) KTP (1.5 mg/kg, IV), and R(-) KTP (1.5 mg/kg, IV). Results - Both KTP enantiomers had elimination halflife and mean residence time measurements that were short and volume of the central compartment and steady state volume of distribution that were low. Clearance was rapid, particularly for R(-) KTP Elimination of both enantiomers from exudate was > 10 times slower than from plasma. Both rac-KTP and the individual enantiomers significantly inhibited serum TXB2 concentrations for 12 hours. Rac-KTP and S(+) KTP, but not R(-) KTP, also significantly inhibited PGE2 synthesis in exudate for 12 hours. Conclusions and Clinical Relevance - Inhibition of serum TXB2 concentration and exudate PGE2 synthesis for similar time courses after S(+) KTP administration indicates that it is a nonselective inhibitor of COX in sheep.